Sustainable urban infrastructural development for smart city in Guwahati, India - Mijing Gwra Basumatary; Subhash Anand (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2018)
The Smart City Mission of Guwahati plains to leverage city’s unique locational advantages to establish its dominance and serve as the hub for the entire North-Eastern region and become a world-class destination in terms of tourism, business, trade, educa-tion and health. To achieve this, the mission plans to use the city’s rich cultural heritage and natural beauty as the key anchors not only for attracting tourists, but also to help convert the city’s present infrastructure challenges into opportunities. The main objective of the study is to analyse the presence of basic urban infrastructural facilities necessary for sustainable smart city.The stratified ran-dom sampling of houses in each 31 wards of the study area was conducted using the questionnaires method. The findings includes that public transport has increased approximately from 10 to 30 per cent. Under Jawaharlal Nehru Urban Renewal Mission (JNNURM) Phase-1 funding 200 buses have been acquired, increasing city’s bus fleet to nearly 2500. Wholesale markets, Inter State Bus Terminus (ISBT) have been shifted to outskirts to de-congest the city. At present 40 percent have piped water supply for 1 hour a day. City engages NGO’s for door to door solid waste collection, which is transported by GPS enabled vehicles. CCTV Cameras are getting installed at 18 identified locations. GMC is upgrading street lighting infrastructure i.e. LED and Solar lights. 2.59 lakhs hous-es and construction of metro was proposed in Guwahati Master Plan 2025. Bio-Metric attendance machine are operational in almost all government offices. Water pump are used to tackle the flash flood.